2015
DOI: 10.1186/s13104-015-1718-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of vascular anomalies in children at a tertiary care hospital in a resource-limited setting: a Tanzanian experience with 134 patients

Abstract: BackgroundVascular anomalies pose major diagnostic and therapeutic challenges among pediatricians and pediatric surgeons practicing in resource limited countries. There is paucity of published data regarding this subject in Tanzania and Bugando Medical Centre in particular. This study describes our experiences on the challenges and outcome of surgical management of childhood vascular anomalies in our environment.MethodsBetween January 2009 and December 2013, a prospective study on the surgical management of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Skin bulging and scarring characterized by remaining fibrofatty tissue is particularly common, occurring in 25% to 68.6% of cases. [52][53][54][55][56][57] In our case series, sequelae after treatment-induced cure were similarly common: 12 of the 27 patients (44.4%) had a sequela, 9 of which involved skin bulging and scarring. Thus, combination therapy did not increase the rate of sequela compared with the literature.…”
Section: Pathogenic Mechanismmentioning
confidence: 94%
“…Skin bulging and scarring characterized by remaining fibrofatty tissue is particularly common, occurring in 25% to 68.6% of cases. [52][53][54][55][56][57] In our case series, sequelae after treatment-induced cure were similarly common: 12 of the 27 patients (44.4%) had a sequela, 9 of which involved skin bulging and scarring. Thus, combination therapy did not increase the rate of sequela compared with the literature.…”
Section: Pathogenic Mechanismmentioning
confidence: 94%
“…In order to effectively treat vascular anomalies, a collaborative approach involving paediatricians, plastic surgeons, interventional radiologists, paediatric surgeons, otorhinolaryngologists, and paediatric oncologists is necessary. In many centres, a variety of treatment modalities, including conservative treatment, surgical excision, injection sclerotherapy, cryotherapy, laser therapy, angiographic embolization, angioplasty/binding of feeder's vessels, the use of angiogenesis inhibitor drugs, and particularly the use of readily available corticosteroids, have produced positive results (19). Sainsbury et al reported that, with acceptable morbidity and recurrence profiles, intralesional bleomycin injection effectively cured complex and recurrent vascular anomalies (20).…”
Section: Managementmentioning
confidence: 99%